Multisensory and modality specific processing of visual speech in different regions of the premotor cortex - Callan, Daniel E.; Jones, Jeffery A.; Callan, Akiko (Frontiers in Psychology, 2014)
Behavioral and neuroimaging studies have demonstrated that brain regions involved with speech production also support speech perception, especially under degraded conditions. The premotor cortex has been shown to be active during both observation and execution of action (‘Mirror System’ properties), and may facilitate speech perception by mapping unimodal and multimodal sensory features onto articulatory speech gestures. For this functional magnetic resonance imaging (fMRI) study, participants identified vowels produced by a speaker in audio-visual (saw the speaker’s articulating face and heard her voice), visual only (only saw the speaker’s articulating face), and audio only (only heard the speaker’s voice) conditions with varying audio signal-to-noise ratios in order to determine the regions of the premotor cortex involved with multisensory and modality specific processing of visual speech gestures. The task was designed so that identification could be made with a high level of accuracy from visual only stimuli to control for task difficulty and differences in intelligibility. The results of the fMRI analysis for visual only and audio-visual conditions showed overlapping activity in inferior frontal gyrus and premotor cortex. The left ventral inferior premotor cortex showed properties of multimodal (audio-visual) enhancement with a degraded auditory signal. The left inferior parietal lobule and right cerebellum also showed these properties. The left ventral superior and dorsal premotor cortex did not show this multisensory enhancement effect, but there was greater activity for the visual only over audio-visual conditions in these areas. The results suggest that the inferior regions of the ventral premotor cortex are involved with integrating multisensory information, whereas, more superior and dorsal regions of the premotor cortex are involved with mapping unimodal (in this case visual) sensory features of the speech signal with articulatory speech gestures.